Roles of Micro and Small Enterprises of Snack and Pastry Productions and Product Innovation on the Increase of People’s Income in Periuk – Tangerang City - Heri Satrianto; Suhendar Janamarta; Sutrisna Sutrisna (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This research was conducted based on researchers’ will to find out the Roles of Small and Micro Enterprises of Snack and Pastry Productions, and Product Inovation toward the Increase of Economy Income of Periuk People – Tangerang City. There are many factors influencing the increase of economy income of UMKM People. Some of them are the lack of policy program on foster father, which was identified to affect the increase of people’s economy income. There was also a shift on the business pattern, which is from conventional into digital. This was why the number of enterpreneurs of micro and small enterprises grew so rapid and massive that it affected the increase of people’s economy income. The lack information on UMKM programs for the people was identified to affect the increase of people’s economy income. The small number of innovation on snack products produced was suspected to influence the increase of people’s economy income. The independent factors studied were the Roles of Small and Micro Enterprises (X1) and Product Innovation (X2), and the dependent factor was People’s Income (Y). Based on the results of correlation coefficient analysis, it was found out that coefficient correlation for X1 is 0.750 and for X2 was 0,805. This means that the roles of micro and small enterprises and product innovation strongly influenced the people’s income. The positive impact showed that the better the roles of micro and small enterprises and product innovation, the higher the people’s income. To find out how much they influenced, Simple Linear Regression was used as analysis tool. It was found out that the results of Variable (X1) and the value of tcount (8.253) was higher than ttable (1.984) and it rejected Ho. So, the hypothesis is Ho was rejected and Ha was accepted. This showed that there were significant influences between roles of micro and small enterprises and the product innovation with the people’s income. The variable X2 with the value of Tcount 4.862 was higher than Ttable and it belonged to the rejection scope of Ho. So, the hypothesis was Ho was rejected and Ha was accepted. This indicated that there were significant influences between product innovation and people’s income.